Strategy For Improving Employee Performance And Commitment To The Organization Through Strengthening Organizational Culture And Work Motivation - Kusuma Adi Prasetyo (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to identify strategies for improving employee performance and commitment through the role of organizational culture and work motivation in the Traffic Control and Order Section of the Bogor City Transportation Agency. This study uses a quantitative approach with survey methods and path analysis. Sample selection used the probability sampling method with area sampling technique. The questionnaire was distributed to 140 employees. The analytical tool used is Structural Equation Modeling (SEM) and processed with the help of SmartPLS version 4.0 software. The research results show that organizational culture has a positive but insignificant effect on employee performance and employee commitment to the organization, but it has a positive and significant effect through work motivation as a mediating variable. Organizational culture has been proven to influence work motivation, while work motivation can enhance employee performance and commitment to the organization. This means that to improve employee performance and commitment to the organization, it can be achieved by enhancing organizational culture and work motivation both directly and indirectly